2016
DOI: 10.1007/s10278-016-9877-x
|View full text |Cite
|
Sign up to set email alerts
|

A Practice Quality Improvement Project: Reducing Dose of Routine Chest CT Imaging in a Busy Clinical Practice

Abstract: The purpose of this report is to describe our experience with the implementation of a practice quality improvement (PQI) project in thoracic imaging as part of the American Board of Radiology Maintenance of Certification process. The goal of this PQI project was to reduce the effective radiation dose of routine chest CT imaging in a busy clinical practice by employing the iDose(4) (Philips Healthcare) iterative reconstruction technique. The dose reduction strategy was implemented in a stepwise process on a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…These included small, single-institution studies with universal improvement on targeted process measures, improvement on some outcome measures, self-reported increases in QI engagement and application, or improvements in knowledge. [99][100][101][102][103][104][105][106][107] However, one local study of inpatient pediatricians showed that improvements made in body mass index documentation were not sustained after the intervention. 108 Small, single-institution QI interventions designed to meet both ACGME and practice improvement (Part IV) MOC requirements demonstrated universal improvement on targeted process measures reflecting the care delivered by trainees.…”
Section: Moc Practice Improvement Activities (Part Iv)mentioning
confidence: 99%
“…These included small, single-institution studies with universal improvement on targeted process measures, improvement on some outcome measures, self-reported increases in QI engagement and application, or improvements in knowledge. [99][100][101][102][103][104][105][106][107] However, one local study of inpatient pediatricians showed that improvements made in body mass index documentation were not sustained after the intervention. 108 Small, single-institution QI interventions designed to meet both ACGME and practice improvement (Part IV) MOC requirements demonstrated universal improvement on targeted process measures reflecting the care delivered by trainees.…”
Section: Moc Practice Improvement Activities (Part Iv)mentioning
confidence: 99%